2012
DOI: 10.1002/alr.21077
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial permeability alterations in an in vitro air–liquid interface model of allergic fungal rhinosinusitis

Abstract: Background Chronic rhinosinusitis (CRS) is an inflammatory upper-airway disease with numerous etiologies. Patients with a characteristic subtype of CRS, allergic fungal rhinosinusitis (AFRS), display increased expression of Th2 cytokines and antigen-specific IgE. Various sinonasal inflammatory conditions are associated with alterations in epithelial barrier function. The aim of this study was to compare epithelial permeability and intercellular junctional protein expression amongst cultured primary sinonasal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 31 publications
0
34
0
1
Order By: Relevance
“…497 The barrier is maintained via ongoing production of AJC proteins as well as protective antiprotease molecules. The polypoid form of CRS and a Th2 cytokine milieu have been associated with significantly decreased levels of AJC proteins [498][499][500][501] as well as diminished intrinsic protective antiprotease activity. 486,502 Functional studies have also documented increased barrier permeability in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…497 The barrier is maintained via ongoing production of AJC proteins as well as protective antiprotease molecules. The polypoid form of CRS and a Th2 cytokine milieu have been associated with significantly decreased levels of AJC proteins [498][499][500][501] as well as diminished intrinsic protective antiprotease activity. 486,502 Functional studies have also documented increased barrier permeability in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…486,502 Functional studies have also documented increased barrier permeability in CRSwNP. 500,501,503 It has been further proposed that the protein oncostatin M may play a key role mediating a leaky barrier in polyps. 503 Furthermore, a global gene microarray meta-analysis indicated that polyp epithelia exhibited a less mature gene signature typically associated with an epithelial to mesenchymal transition, which would predict a loss of barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In Calu3 cells, IL-4 induces disassembly of TJ molecules [100], IL-4 and IL-13 increase paracellular permeability in human bronchial epithelial cells [107, 118], in sinosonal epithelial cells [142] and in air-liquid interface cultivated paranasal sinus mucosa cells [16]. Although IL-4 and IL-13 show similar effects on TJ in these airway epithelial cell models, depending on the investigated model, they act via different pathways.…”
Section: Tight Junctions and Asthmamentioning
confidence: 99%
“…Subsequent studies have suggested a weakened mechanical barrier as well, with diminished tight junctional proteins and increased susceptibility to exogenous protease degradation [7981]. Functional studies demonstrated that the barrier was porous in CRSwNP, permitting increased access of foreign material across the epithelium [82, 83]. Recently, elevated levels of Oncostatin M, which is a cytokine that can cause the disassembly of tight junctions, have been reported in affected tissues, and may be hypothesized to play a role in barrier defects in CRS [84].…”
Section: Immune Barrier Hypothesismentioning
confidence: 99%